Investigating possibilities for using sea shell on compressive strength properties of concrete - Kumar, Kiran; Anil, Vineetha; Hamed, Sara; Malik, Ruwa (International Journal of Engineering and Technology, 2018)
The reason of this attempt was to demonstrate that seashells can be utilized as a partial replacement for fine aggregate in concrete for enhancing strength properties. Since seashells are widely available everywhere in coastal and seashore areas, and some of the concrete materials cannot be found easily everywhere.Â  The strategies utilized as a part of this attempt was to replace burnt and crushed seashells with fine aggregate at 10%, 20% and 30% and compare it with each other and the traditional Ordinary Portland Cement concrete regarding mechanical properties following 7 and 28 days. In conclusion, despite the fact that seashells are generally accessible and can be effortlessly gathered from seashore and beach front regions, the process of burning and crushing requires a lot of energy and is tedious. In spite of the fact that the results demonstrated that utilizing 20% seashell to fine aggregate substitution has a somewhat higher in compressive and flexural properties than that of Ordinary Portland Cement concrete.
Keywords: Seashell; Sustainability; Fine Aggregate; Mechanical Properties; Supplementary Material.